The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13021-015-0021-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of field plot size on prediction accuracy of aboveground biomass in airborne laser scanning-assisted inventories in tropical rain forests of Tanzania

Abstract: BackgroundAirborne laser scanning (ALS) has recently emerged as a promising tool to acquire auxiliary information for improving aboveground biomass (AGB) estimation in sample-based forest inventories. Under design-based and model-assisted inferential frameworks, the estimation relies on a model that relates the auxiliary ALS metrics to AGB estimated on ground plots. The size of the field plots has been identified as one source of model uncertainty because of the so-called boundary effects which increases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 45 publications
7
61
0
2
Order By: Relevance
“…The plot locations were chosen to capture the variation in biomass by distributing them in different altitudinal zones [16]. To evaluate the representativeness of the 30 circular plots Mauya et al [16] compared the properties of the sample to a second sample of 153 systematically distributed plots covering the study area.…”
Section: Field Datamentioning
confidence: 99%
See 4 more Smart Citations
“…The plot locations were chosen to capture the variation in biomass by distributing them in different altitudinal zones [16]. To evaluate the representativeness of the 30 circular plots Mauya et al [16] compared the properties of the sample to a second sample of 153 systematically distributed plots covering the study area.…”
Section: Field Datamentioning
confidence: 99%
“…For this purpose the variance was estimated in a design-based framework. Mauya et al [16] concluded that reduced model noise from co-registration errors and boundary effects meant that larger plot size was preferable for ALS-supported biomass estimates.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations